Short-Term Medical Cannabis Treatment Regimens Produced Beneficial Effects among Palliative Cancer Patients - Joshua Aviram; Gil M. Lewitus; Yelena Vysotski; Anton Uribayev; Shiri Procaccia; Idan Cohen; Anca Leibovici; Mahmud Abo-Amna; Luiza Akria; Dmitry Goncharov; Neomi Mativ; Avia Kauffman; et al. (MDPI AG, 2020)
In the last decade the use of medical cannabis (MC) for palliative cancer treatment has risen. However, the choice between products is arbitrary and most patients are using Tetrahydrocannabinol (THC)-dominant cannabis products. In this study, we aimed to assess the short-term outcomes of MC treatment prescribed by oncologists in relation to the type of cannabis they receive. A comparative analysis was used to assess the differences in treatment effectiveness and safety between THC-dominant (n = 56, 52%), cannabidiol (CBD)-dominant (n = 19, 18%), and mixed (n = 33, 30%) MC treatments. Oncology patients (n = 108) reported on multiple symptoms in baseline questionnaires, initiated MC treatment, and completed a one-month follow-up. Most parameters improved significantly from baseline, including pain intensity, affective and sensory pain, sleep quality and duration, cancer distress, and both physical and psychological symptom burden. There was no significant difference between the three MC treatments in the MC-related safety profile. Generally, there were no differences between the three MC treatments in pain intensity and in most secondary outcomes. Unexpectedly, CBD-dominant oil treatments were similar to THC-dominant treatments in their beneficial effects for most secondary outcomes. THC-dominant treatments showed significant superiority in their beneficial effect only in sleep duration compared to CBD-dominant treatments. This work provides evidence that, though patients usually consume THC-dominant products, caregivers should also consider CBD-dominant products as a useful treatment for cancer-related symptoms.